Variable wavelength perovskite quantum dot glass based on Joule thermal sintering and preparation thereof

Through Joule thermal sintering method and SBA-15 pore structure coating technology, the problems of complex and energy consumption of traditional perovskite quantum dot glass preparation process are solved, and the rapid sintering and wavelength change effect are achieved, and the stability and preparation efficiency are improved.

CN119874191APending Publication Date: 2025-04-25SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411932636.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The preparation process of traditional perovskite quantum dot glass is complex, has high energy consumption and low efficiency, and the perovskite quantum dots are easy to decompose in an aqueous oxygen environment, which limits its use range.

Method used

The perovskite quantum dots are coated using the pore structure of SBA-15, and the sintering temperature and insulation time are controlled to achieve rapid sintering and wavelength change effects.

Benefits of technology

The sintering process efficiency of perovskite quantum dot glass is improved, the preparation cost is reduced, the stability of perovskite quantum dots is enhanced, and the control of different PL peak wavelengths is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874191A_ABST
    Figure CN119874191A_ABST
Patent Text Reader

Abstract

The invention discloses variable-wavelength perovskite quantum dot glass based on Joule thermal sintering and a preparation method of the variable-wavelength perovskite quantum dot glass. The preparation method comprises the following steps: adding CsBr, PbBr2 and SBA-15 into a beaker filled with ultrapure water, fully stirring, and drying to obtain powder; putting the powder into a crucible in an inert atmosphere, putting the crucible on a carbon heating body, electrifying the carbon heating body by using direct current, rapidly heating the carbon heating body under the action of the current, and sintering the powder to obtain perovskite semi-finished product powder; after the perovskite semi-finished product powder is cooled, adding the perovskite semi-finished product powder into ultrapure water, washing for multiple times, and drying; fully grinding the dried perovskite semi-finished product powder and glass powder in an agate mortar, uniformly mixing, and carrying out mold pressing in a mold to obtain a formed structure; and in an inert atmosphere, putting the obtained molded structure into a crucible, and then carrying out secondary rapid sintering in a carbon heating body to obtain the perovskite quantum dot glass. The preparation process of the perovskite quantum dot glass is effectively improved, and the application prospect of the perovskite quantum dot glass is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to optical glass, and in particular to a wavelength-variable perovskite quantum dot glass based on Joule heat sintering and a preparation method thereof. Background Art

[0002] Perovskite materials have attracted extensive research interest due to their outstanding performance in optoelectronic devices, solar cells and other fields. Perovskite quantum dot glass is similar to fluorescent glass. Due to its special structure and properties, it can emit visible light after being excited by ultraviolet light or other specific wavelengths of light. Sintering technology is a crucial step in the preparation of perovskite quantum dot glass. By optimizing the sintering conditions, perovskite quantum dot glass with excellent performance can be obtained, thereby improving the optical performance of the device.

[0003] Perovskite quantum dots are a special type of quantum dots, semiconductor nanomaterials with a perovskite structure. Their luminescence principle involves the electron excitation and reradiation of the perovskite structure, as well as the size effect of the quantum dots. Perovskite quantum dots are usually prepared by solvothermal methods and other methods.

[0004] During the preparation process, by controlling the reaction conditions, nanoparticles with smaller sizes can be obtained to form quantum dots. These quantum dots exhibit quantum confinement effects because their size is smaller than the exciton radius. When an external light source (such as ultraviolet light) is irradiated onto the perovskite quantum dots, energy is absorbed, causing electrons to jump from the valence band to the conduction band. Under light excitation conditions, electrons jump from the valence band to the conduction band to form free electrons, while holes are formed in the valence band. Due to the small size of quantum dots, the Coulomb interaction between electrons and holes is enhanced. Electrons and holes may recombine, and electrons return to the valence band, releasing energy. This energy release process leads to luminescence. The wavelength of luminescence usually depends on the size of the quantum dots, that is, the band gap.

[0005] The traditional method for preparing perovskite quantum dot glass is: first, prepare perovskite quantum dots by a solution method, which requires the addition of an additional ligand solution to form ligands outside the perovskite quantum dots and prevent the agglomeration of quantum dots, and then mix the perovskite quantum dots with glass powder and place them in a muffle furnace or a tube furnace for firing. The firing process is time-consuming, energy-intensive, and inefficient. Since perovskite quantum dots decompose rapidly in a water-containing oxygen environment, the scope of use of perovskite quantum dots is subject to certain restrictions. In the present invention, SBA-15 is melted by rapid sintering, and the perovskite quantum dots in the SBA-15 pore structure are coated, which can better protect the perovskite quantum dots.

[0006] Therefore, in view of the problems existing in the preparation process of perovskite quantum dot glass, such as complex process, high energy consumption and low efficiency, it is urgent to propose a method for quickly preparing perovskite quantum dot glass with high efficiency and low energy consumption, which has important scientific research and engineering significance. Summary of the invention

[0007] The object of the present invention is to overcome the above-mentioned shortcomings and deficiencies of the prior art and to provide a variable wavelength perovskite quantum dot glass based on Joule heat sintering and its preparation.

[0008] The present invention aims to solve the problems that the traditional glass sintering method usually requires a long time to process, has low efficiency, high energy consumption, and high purchase cost of heating equipment. It also uses the structural characteristics of SBA-15 to coat the perovskite quantum dots, which can further control the size of the perovskite quantum dots while improving their stability. In addition, a method for rapid sintering of perovskite quantum dot glass with variable wavelength is proposed by controlling the sintering temperature and holding time of the rapid sintering process.

[0009] The present invention is achieved through the following technical solutions: A method for preparing wavelength-variable perovskite quantum dot glass based on Joule heat sintering comprises the following steps: S1: CsBr and PbBr 2 and SBA-15 was added into a beaker containing ultrapure water, stirred thoroughly, and dried to obtain a powder; S2: In an inert atmosphere, the powder obtained in step S1 is placed in a crucible, and the crucible is placed on a carbon heating body. The carbon heating body is powered by direct current, and the carbon heating body is rapidly heated under the action of the current, and the powder is sintered to obtain a semi-finished perovskite powder; S3: After the semi-finished perovskite powder obtained in step S3 is cooled, it is added into ultrapure water, washed several times and then dried; S4: placing the dried semi-finished perovskite powder and the glass powder in an agate mortar and grinding them thoroughly, mixing them evenly and placing them in a mold for molding to obtain a molded structure; S5: In an inert atmosphere, the molded structure obtained in step S4 is placed in a crucible, and then a secondary rapid sintering is performed in a carbon heating body to obtain perovskite quantum dot glass.

[0010] The ratio of each component in step S1 is: CsBr and PbBr 2 The molar ratio is 1:1~6:1; CsBr / PbBr 2 The mass ratio with SBA-15 is 1:1~1:5; CsBr / PbBr 2 The mass ratio of SBA-15 and glass powder is 1:1~1:10.

[0011] The sufficient stirring in step S1 refers to: using ultrasonic stirring, and the stirring time is 30 min-60 min, such as 35 min, 40 min, 45 min, 50 min or 55 min.

[0012] The drying treatment in step S1 refers to: a drying temperature of 40-90°C (preferably 45°C, 50°C, 60°C, 75°C or 80°C), and a drying time of 30 min-2 h, such as 50 min, 1 h, 1.5 h or 1.8 h.

[0013] The inert atmosphere in step S2 refers to: argon, nitrogen or carbon dioxide.

[0014] The carbon heating body in step S2 refers to: carbon felt, carbon cloth, carbon paper or carbon plate.

[0015] The parameters of the direct current in step S2 are: voltage of 0V-40V, current of 0A-30A, and power-on time of 20s-60s.

[0016] The mold in step S2 is made of stainless steel or resin material, the molding pressure is 40MPa-100Mpa, and the pressure holding time is 30s-5min, such as 1min, 2min, 3min or 4min.

[0017] In step S3, the drying temperature is 40-90° C., and the drying time is 5 min-10 min, such as 6 min, 7 min, 8 min or 9 min.

[0018] The variable wavelength perovskite quantum dot glass can be obtained by adopting the above method.

[0019] Compared with the prior art, the present invention has the following advantages and effects: Compared with the traditional perovskite quantum dot glass sintered in a tube furnace, the present invention realizes the rapid sintering of perovskite quantum dot glass based on the Joule heat process, which greatly improves the sintering process efficiency of perovskite quantum dot glass. At the same time, since the carbon heating body used in the present invention is a carbon bar, carbon felt, etc., its cost is lower than that of the traditional sintering method.

[0020] Compared with the traditional method of manufacturing perovskite quantum dot glass with a single PL peak wavelength, the present invention can control the output parameters of the DC power supply to control the sintering temperature and the holding time, thereby controlling the size of the perovskite quantum dots, so that the perovskite quantum dots have different PL peak wavelengths.

[0021] The present invention utilizes the structural characteristics of SBA-15 to synthesize perovskite quantum dots in its pores. During rapid sintering, the pore structure of SBA-15 melts and coats the perovskite quantum dots, thereby isolating the perovskite quantum dots from the outside and greatly improving the stability of the perovskite quantum dots. At the same time, since the pore size of SBA-15 is extremely small, after rapid sintering, the pore structure melts and coats the perovskite quantum dot powder in the pores, which can also control the size of the perovskite quantum dots. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a manufacturing flow chart of variable wavelength perovskite quantum dot glass based on rapid sintering by Joule heat process in an embodiment of the present invention.

[0023] Figure 2 Schematic diagram of sample stirring in an embodiment of the present invention.

[0024] Figure 3 Schematic diagram of a sample rapid sintering device in an embodiment of the present invention.

[0025] Figure 4 Schematic diagram of molding mixed powder into a compact structure in an embodiment of the present invention.

[0026] The numbers in the figure are: 1 is the ultrasonic stirrer horn; 2 is a beaker; 3 is pure water; 4 is CsBr powder; 5 is SBA-15; 6 is PbBr 2 powder; 7 is a crucible; 8 is a sample to be heated; 9 is a carbon heating body; 10 is a DC power supply; 11 is an upper mold; 12 is a mixed powder; and 13 is a lower mold. DETAILED DESCRIPTION

[0027] The present invention uses a Joule heat process to rapidly sinter perovskite quantum dot glass, and by controlling the sintering temperature and the holding time, perovskite quantum dot glass with different PL peak wavelengths can be manufactured. The present invention is further described in detail below in conjunction with specific embodiments.

[0028] Example like Figure 1-4 As shown, the present invention discloses a method for manufacturing a variable wavelength perovskite quantum dot glass by rapid sintering based on a Joule heat process, which can be achieved by the following steps: First, CsBr and PbBr 2 And SBA-15 with a mass ratio of about 3:5:24 (i.e. CsBr and PbBr 2 Mix CsBr / PbBr in a molar ratio of 1:1. 2and SBA-15 in a mass ratio of 1:3) were added to a beaker filled with ultrapure water and stirred at 80°C for 30 min using an ultrasonic stirrer to allow CsBr / PbBr to form 2 SBA-15 was fully filled in, and then the mixture was dried at a constant temperature of 80°C to form powder.

[0029] Then, in an inert atmosphere, the powder obtained above was placed in a crucible, and the crucible was placed on a carbon heating body. A direct current was applied to both sides of the carbon heating body through an electrode sheet external power supply. The current of the applied direct current was 10 A and the duration was 30 s. The carbon heating body was quickly heated to 800°C using the Joule heating process. The high temperature caused CsBr and PbBr to react. 2 The reaction generates CsPbBr 3 At the same time, the pore structure of SBA-15 was also melted, making some CsPbBr 3 Wrapped in SBA-15.

[0030] The sintered powder was washed several times with ultrapure water to remove CsPbBr 3 or other salts.

[0031] The obtained powder is then dried and placed in a mortar with the glass powder for thorough grinding. After being evenly mixed, the mixed powder is placed in a mold for molding. The mixed powder is molded for 40 seconds at a pressure of 40 MPa to obtain a planar molding structure.

[0032] Finally, the obtained molded structure was placed in a crucible, and the crucible was placed on a carbon heating body for rapid sintering, wherein the DC current applied was 6.4 A and the duration was 30 s. The carbon heating body was quickly heated to 600°C using the Joule heat process. After sintering, the semi-finished lens was collected, and then the semi-finished lens was ground and polished to finally obtain a finished lens with a smooth surface, that is, a planar perovskite quantum dot glass.

[0033] As described above, the present invention applies the Joule heating process to the preparation process of perovskite quantum dot glass, improves production efficiency, avoids high energy consumption caused by long-term heating treatment, and thus significantly reduces the preparation cost of perovskite quantum dot glass.

[0034] The present invention controls the size of the perovskite quantum dots by controlling the temperature and the holding time during rapid sintering, so that the perovskite quantum dots rapidly sintered have different PL peak wavelengths.

[0035] The present invention cleverly utilizes the structural characteristics of SBA-15 to synthesize perovskite quantum dots in its pores. During rapid sintering, the pore structure of SBA-15 melts and coats the perovskite quantum dots, thereby isolating the perovskite quantum dots from the outside and improving the stability of the perovskite quantum dots. At the same time, this method utilizes the pore size advantage of SBA-15 to effectively control the size of the perovskite quantum dots.

[0036] The implementation methods of the present invention are not limited to the above-mentioned embodiments, and any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A method for preparing wavelength-variable perovskite quantum dot glass based on Joule heat sintering, characterized in that The steps include: S1: Add CsBr, PbBr2 and SBA-15 into a beaker filled with ultrapure water, stir thoroughly, and dry to obtain powder; S2: In an inert atmosphere, the powder obtained in step S1 is placed in a crucible, and the crucible is placed on a carbon heating body. The carbon heating body is powered by direct current, and the carbon heating body is rapidly heated under the action of the current, and the powder is sintered to obtain a semi-finished perovskite powder; S3: After the semi-finished perovskite powder obtained in step S3 is cooled, it is added into ultrapure water, washed several times and then dried; S4: placing the dried semi-finished perovskite powder and the glass powder in an agate mortar and grinding them thoroughly, mixing them evenly and placing them in a mold for molding to obtain a molded structure; S5: In an inert atmosphere, the molded structure obtained in step S4 is placed in a crucible, and then a second rapid sintering is performed in a carbon heating body to obtain perovskite quantum dot glass.

2. The method for preparing wavelength-variable perovskite quantum dot glass based on Joule heat sintering according to claim 1, characterized in that: The ratio of the components in step S1 is: the molar ratio of CsBr to PbBr2 is 1:1 to 6:1; The mass ratio of CsBr / PbBr2 and SBA-15 is 1:1~1:5; The mass ratio of CsBr / PbBr2 / SBA-15 and glass powder is 1:1~1:

10.

3. The method for preparing wavelength-variable perovskite quantum dot glass based on Joule heat sintering according to claim 1, characterized in that: The sufficient stirring in step S1 refers to: ultrasonic stirring, and the stirring time is 30 min-60 min.

4. The method for preparing wavelength-variable perovskite quantum dot glass based on Joule heat sintering according to claim 1, characterized in that: The drying treatment in step S1 refers to: a drying temperature of 40° C. to 90° C. and a drying time of 30 min to 2 h.

5. The method for preparing wavelength-variable perovskite quantum dot glass based on Joule heat sintering according to claim 1, characterized in that: The inert atmosphere in step S2 refers to: argon, nitrogen or carbon dioxide.

6. The method for preparing wavelength-variable perovskite quantum dot glass based on Joule heat sintering according to claim 1, characterized in that: The carbon heating body in step S2 refers to: carbon felt, carbon cloth, carbon paper or carbon plate.

7. The method for preparing wavelength-variable perovskite quantum dot glass based on Joule heat sintering according to claim 1, characterized in that: The parameters of the direct current in step S2 are: voltage of 0V-40V, current of 0A-30A, and power-on time of 20s-60s.

8. The method for preparing wavelength-variable perovskite quantum dot glass based on Joule heat sintering according to claim 1, characterized in that: The mold in step S2 is made of stainless steel or resin material, the molding pressure is 40 MPa-100 MPa, and the pressure holding time is 30s-5min.

9. The method for preparing wavelength-variable perovskite quantum dot glass based on Joule heat sintering according to claim 1, characterized in that: The drying temperature in step S3 is 40° C.-90° C., and the drying time is 5 min-10 min.

10. The wavelength-variable perovskite quantum dot glass obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Process for synthesizing fluorescent perovskite quantum dot composite material based on Joule thermal method

    CN121182480A